Prevalence of white matter hyperintensities increases with age - Zhuang, Feng-Juan (Neural Regen Res, 2018)
White matter hyperintensities (WMHs) that arise with age and/or atherosclerosis constitute a heterogeneous disorder in the white matter of the brain. However, the relationship between age-related risk factors and the prevalence of WMHs is still obscure. More clinical data is needed to confirm the relationship between age and the prevalence of WMHs. We collected 836 patients, who were treated in the Renmin Hospital, Hubei University of Medicine, China from January 2015 to February 2016, for a case-controlled retrospective analysis. According to T2-weighted magnetic resonance imaging results, all patients were divided into a WMHs group (n = 333) and a non-WMHs group (n = 503). The WMHs group contained 159 males and 174 females. The prevalence of WMHs increased with age and was associated with age-related risk factors, such as cardiovascular diseases, smoking, drinking, diabetes, hypertension and history of cerebral infarction. There was no significant difference in sex, education level, hyperlipidemia and hyperhomocysteinemia among the different age ranges. These findings confirm that age is an independent risk factor for the prevalence and severity of WMHs. The age-related risk factors enhance the occurrence of WMHs.